The Impact of Industry-Based Training Programs and Indonesian National Work Competency Standards on Productive Teacher Performance in Ministry of Industry Vocational High School Through Motivation as an Intervening Variable - Pioni Putra; Yulasmi Yulasmi; Lusiana Lusiana (Jurnal Multidisiplin Sahombu, 2026)
This study aims to examine the impact of industry-based training programs and Indonesian national work competency standards on the performance of productive teachers at vocational high schools (SMK) under the Ministry of Industry, using motivation as an intervening variable. Data collection methods included a survey and questionnaire distribution, with a sample of 85 respondents. The analysis method used was structural equation modeling using SmartPLS. The results showed a significant effect of training on work motivation. There was a significant effect of competence on work motivation. There was a significant effect of training on teacher performance. There was a significant effect of competence on teacher performance. There was a significant effect of work motivation on teacher performance. There was a significant effect of training on teacher performance through work motivation. There was a significant effect of competence on teacher performance through work motivation.